Envisioning Systemic Transition Period Wars through the Thirty Years’ War and the First and Second World Wars - Bilgehan Emeklier; Nihal Emeklier (Güvenlik Stratejileri Dergisi)
This article focuses on “systemic transition period wars” emerging during specific historical periods and bringing about transformative changes in the international power configuration, leading to a new systemic structure. It aims to elucidate the distinct characteristics and outcomes of systemic transition period wars by exploring two historical examples –the Thirty Years’ War and the First and Second World Wars. The article’s focus is to reveal under which circumstances these systemic transition period wars occur and how these systemic wars not only alter the distribution of power among international actors but also fundamentally reshape the global systemic structure.